A Comparison of Symptom Severity and Bolus Retention to Chicago Classification Esophageal Pressure Topography Metrics in Patients with Achalasia - Nicodème, Frédéric (2012)
BACKGROUND & AIMS: We compared findings from timed barium esophagrams (TBEs) and esophageal pressure topography (EPT) studies among achalasia subtypes and in relation to symptom severity. METHOD: We analyzed data from 50 patients with achalasia (31 male, 20–79 years old) who underwent high-resolution manometry (HRM), had TBE following a 200ml barium swallow, and completed questionnaires that determine Eckardt Scores (ES). Twenty-five were not treated and 25 were treated (11 by pneumatic dilation, 14 by myotomy). Non-parametric testing was used to assess differences among groups of treated patients (10 had type-1 achalasia and 15 had type-2 achalasia), and the Pearson correlation was used to assess their relationship. RESULTS: There were no significant differences in TBE measurements between patient groups. Of the 25 patients who received treatment, 10 had a manometric pattern consistent with persistent achalasia after treatment (6 with type 1 and 4 with type 2 achalasia), whereas 15 appeared to have resolved the achalasia pattern (peristalsis was absent in 8 and weak in 7). The height of the barium column at 5 minutes and ES were significantly reduced in patients that had resolved their achalasia pattern, based on HRM. The integrated relaxation pressure (IRP) and the TBE column height correlated at 5 minutes (r=0.422; p<0.05). DISCUSSION: Patients that resolve their achalasia pattern, based on HRM, demonstrated improved emptying based on TBE measurements and improved symptom scores. There was no significant difference between patients with type-1 or 2 achalasia in TBEs. These findings indicate that normalization of the IRP on HRM is a clinically relevant objective of treatment for achalasia.